THE ROLES OF TED TALKS AND VLOG IN SPEAKING CLASS: STUDENTS’ PERSPECTIVESs - Candradewi Wahyu Anggareni Arum Nisma Wulanjani (STMIK BINA PATRIA, 2017)
The aims of this research were to describe the students’ perspectives toward the roles of TED Talks and Vlog in enhancing students’ activeness in speaking class. The research method used in this research was qualitative research design in the form of case study. The instruments of data collection were documents of students’ vlogs, observation, questionnaire, and interview. The participants of this research were the students of speaking class.This research had three research significances which consisted of theoretical significance, practical significance, and pedagogical significance. The theoretical significance was the research contributes to prove and added the speaking theories, whereas the practical significance was the research can be conducted by teachers, lecturers, or researchers to figure out the roles and the ways to improve students’ participation in speaking class. In addition, the pedagogical significance showed that this research provided a reference of TED Talks and Vlog in enhancing students’ activeness in speaking class, helped the students to be active in speaking class by following the lecturer’s instruction toward the speaking activities given, and could be used as the empirical research finding toward students’ activeness in speaking class. Keywords: Speaking, Students’ perspectives, Technology